(untitled) (Journal of the College of Education for Women, 2019)
Context has a significant impact on the interpretation of Qur’anic and literary texts, especially in ancient Arabic poetry since that language is no longer considered as a contemporary understandable language. Hence this research is entitled: (the impact of context on the morphological semantics in the Diwan of Abi Al-Aswad Al-Dau’ali) and the morphological meanings indicated by the morphological formula which lack the combination of other contextual clues. The researcher depended on the analytical approach to show the impact of pairing occurring between the contextual elements on determining the morphological meaning.The most important findings reached at:1- Context has a great impact in dispelling the possibilities arising from the use of linguistic elements to denote more meanings, especially the morphological ones that are considered as functional meanings that cannot take morphological formula to denote them individually.2 - The actual additional verbal formulas are the most morphological formulas that lack context in determining the intended meanings for their abundance and use in Arabic in addition to the multitude of meanings used through each formula.3 - The derivative clue is the best for determine the intended meaning, whether in verbal or noun constructions.4 - Other important clues are transitivity and intransitivity, particularly in defining the semantics of additional verbs, as well as the clue related to the syntactic location of the word that assist in determining the morphological meaning of its formula.